2018
DOI: 10.14245/ns.1836100.050
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Subaxial Spine Injuries Managed With 2-Level Anterior Cervical Corpectomy and Fusion: A Prospective Study

Abstract: ObjectiveTo evaluate the results of operative management of subaxial spine injuries managed with 2-level anterior cervical corpectomy and fusion with a cervical locking plate and autologous bone–filled titanium mesh cage. MethodsThis study included 23 patients with a subaxial spine injury who matched the inclusion criteria, underwent 2-level anterior cervical corpectomy and fusion at our institution between 2013 and 2016, and were followed up for neurological recovery, axial pain, fusion, pseudarthrosis, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Approximately 90% of subjects with radiculopathy preoperatively were recovered and were asymptomatic at follow-up. Han et al evaluated 27.6 months of follow-up, in which 21 cases (21.4%) showed an improvement in the Frankel grade with complete fusion in all cases [20][21] . In Anissipour et al analysis who shared data on 36 patients with dislocation of facet treated with ACDF by fixed plate and for 324 days were followed-up.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of subjects with radiculopathy preoperatively were recovered and were asymptomatic at follow-up. Han et al evaluated 27.6 months of follow-up, in which 21 cases (21.4%) showed an improvement in the Frankel grade with complete fusion in all cases [20][21] . In Anissipour et al analysis who shared data on 36 patients with dislocation of facet treated with ACDF by fixed plate and for 324 days were followed-up.…”
Section: Discussionmentioning
confidence: 99%
“…An anterior approach with ACCF is widely considered a safe and effective surgical treatment to achieve spinal cord decompression and high fusion rates in degenerative pathologies as well as traumatic spinal injuries. 1 , 2 , 15 , 21 However, whether ACCF provides sufficient stability on its own, especially in multilevel ACCFs, remains controversial. Additional surgery with PF can provide extra support to improve cervical stability and is sometimes performed at the index operation or later as supplementary surgery due to material failure or instability.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 300 ACCF surgeries showed 2-level ACCFs being more susceptible to severe subsidence and related complications compared to single-level ACCFs. 26 A more recent study showed no stability-related complications when analyzing the outcome of 23 patients treated with 2-level ACCF for subaxial injuries, 2 but the presented radiographic follow-up data were limited. A study of 21 patients with CSM treated with ACCF showed instability in 33% of the cases and recommended a combination with PF for ≥2-level surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No COVID-19 patients were treated. The neurological status was assessed using the American Spinal Injury Association (ASIA) impairment scale as it can be used for traumatic [5] as well as non-traumatic SCI [6]. Thoracolumbar injury classification and severity score (TLICS) based on the morphology of the injury, the integrity of the posterior ligamentous complex, and neurological status of the patient was performed in which points are assigned for each category and the final total points suggest the possible treatment option for thoracolumbar vertebral fractures [7].…”
Section: Methodsmentioning
confidence: 99%